Rosella Flower Decreases the CML Serum and Liver Inflammation of Rats Given Baked-Food Diet - Falyani, Silvy Amalia; Soeharto, Setyawati; Widjajanto, Edi; Ratna, Ardhiyanti Puspita; Batmomolin, Pia Bataif (Graduate School, Universitas Brawijaya, 2016)
Advanced Glycation Endproducts (AGEs) or so-called glycotoxin can be triggered by heated food in which the Maillard reaction occurs. One type of glycotoxins is CML. Accumulated N-Carboxymethyl-Lysine (CML) can cause inflammation of organs, e.g. liver. Rosella flowers contain anthocyanin compound that has anti-glycation and antioxidant effects. This study aimed to determine the effect of ethanol extract of Rosella on CML serum level, IL-6 level, and NF-ƙB activation in the liver of mice fed with baked food. This study used post-test design using 25 Wistar rats aged 3-4 months old that were divided into 5 groups, namely negative control group, positive control group, treatment groups given Rosella extract dose of 200mg.kgBW-1, 300mg.kgBW-1, and 400mg.kgBW-1. Baked feed was given for 12 weeks, and Rosella ethanol extract was administered in the 9th to 12th week. The examination on CML serum and IL-6 of the liver was using ELISA method. Immunofluorescent staining was used to determine NF-ƙB activation in the liver using a confocal microscope. CML serum is proven to increase significantly (p = 0.000). The effective dose of Rosella flower extract to prevent CML Serum increase is 200 mg.kgBW-1, whereas a dose of 400 mg.kgBW-1 can decrease IL-6 level and NF-ƙB activation. Ethanol extract of Rosella flower decrease the levels of N-carboxymethyl-lysine serum, IL-6, and NF-ƙB activation in the liver of rats given baked-food diet. Keywords: Advanced Glycation Endproducts (AGEs), Interleukin-6, N-Carboxymethyl-lysine, Rosella.